The Thoughts and Contributions of Sitti Raihanun in the Development of Islamic Education in West Nusa Tenggara - Sopian, Hilmi; Masnun, Masnun; Sainun, Sainun; Hamim, Khairul (Didaktika Religia, 2024)
This study examines the impact of Sitti Raihanun’s philosophy, life experiences and educational initiatives on the educational landscape in West Nusa Tenggara. The study focuses on three main aspects: firstly, the influence of her upbringing in an Islamic environment and her involvement in the founding of Nahdlatul Wathan by her father, Maulana al-Syaikh TGKH. Secondly, her pioneering role in the advancement of women through the Muslimat Nahdlatul Wathan, which broadened avenues for women’s involvement in Islamic education and organisations. Thirdly, her contributions to the establishment of educational institutions, notably Pondok Pesantren Syaikh Zainuddin NW, which became a pivotal centre for Islamic education. The research employs a historical-qualitative methodology, utilising document analysis and interviews with key informants in the field of Islamic education. The findings demonstrate that Sitti Raihanun was able to successfully establish educational institutions from scratch, including the Pondok Pesantren Syaikh Zainuddin NW in Anjani, which subsequently became a central hub for Nahdlatul Wathan’s activities. As a pioneering female leader, she was able to surmount the societal barriers that existed at the time to become the first woman to head the largest Islamic organisation in West Nusa Tenggara, thereby significantly advancing the role of women in education and leadership.